Identifikasi Jenis Pigmen dan Uji Potensi Antioksidan Ekstrak Pigmen Bakteri Serratia marcescens Hasil Isolasi dari Sedimen Sumber Air Panas Gedong Songo - Naufal, Adhitya; Kusdiyantini, Endang; Raharjo, Budi (Berkala Bioteknologi, 2021)
Pigments can be produced by plants, animals, and microbes, including the bacteria Serratia marcescens. Pigments are believed to be used as antibacterial, anticancer, antibiotic and antioxidant. The quality of the pigment is greatly determined by its type. The aim of this study was to identify the type of pigment produced by S. marcescens resulting from the sediment of Gedong Songo hot spring, and testing its antioxidant activity. S. marcescens was grown on Nutrient Broth (NB) medium for 96 hours at room temperature and sampled once every 6 hours for growth measurement and pigment measurement. Cell dry weight was used to measure the growth of S. marcescens, while the measurement of pigment production was done using spectrophotometer with 535 nm wavelength for red pigment and identification of pigment with Thin Layer Chromatography and UV-Vis and testing of antioxidant activity using carotene bleaching method. The results showed the measurement of pigment production has optimal point at 48 hours at 1,319 mg/L. Identification of pigment type S. marcescens using TLC obtained value of 0,8 with spectrophotometer wavelength at 536 nm. The value of antioxidant activity Pigment S. marcescens obtained at 13%.